Update on COVID-19 Therapy in Pediatric Age - Susanna Esposito; Giovanni Autore; Alberto Argentiero; Greta Ramundo; Serafina Perrone; Nicola Principi (MDPI AG, 2022)
With the extension of the COVID-19 pandemic, the large use of COVID-19 vaccines among adults and the emergence of SARS-CoV-2 variants means that the epidemiology of COVID-19 in pediatrics, particularly among younger children, has substantially changed. The prevalence of pediatric COVID-19 significantly increased, several severe cases among children were reported, and long-COVID in pediatric age was frequently observed. The main aim of this paper is to discuss which types of treatment are presently available for pediatric patients with COVID-19, which of them are authorized for the first years of life, and which are the most important limitations of COVID-19 therapy in pediatric age. Four different antivirals, remdesivir (RVD), the combination nirmatrelvir plus ritonavir (Paxlovid), molnupiravir (MPV), and the monoclonal antibody bebtelovimab (BEB), are presently approved or authorized for emergency use for COVID-19 treatment by most of the national health authorities, although with limitations according to the clinical relevance of disease and patient's characteristics. Analyses in the literature show that MPV cannot be used in pediatric age for the risk of adverse events regarding bone growth. The other antivirals can be used, at least in older children, and RDV can be used in all children except in neonates. However, careful research on pharmacokinetic and clinical data specifically collected in neonates and children are urgently needed for the appropriate management of pediatric COVID-19.